Australia's National Electricity Market after Twenty Years. (1st December 2019) - Rai, Alan; Nelson, Tim
Abstract: The Hilmer reforms served electricity consumers well over the first post‐reform decade. However, three key issues emerged from the mid‐2000s: (i) a significant and largely unnecessary rise in network expenditures; (ii) emissions policy discontinuity; and (iii) a large increase in wholesale prices due to rising fuel prices and the sudden exit of generators. The consequence was a doubling in retail prices. Deficiencies in cost‐recovery mechanisms have meant price increases have disproportionately affected low‐income households. We propose three key reforms as rectification: (i) integrating emissions reduction and energy policies; (ii) boosting network capacity utilisation; and (iii) improving cost recovery mechanisms.